O pagamento por serviços ambientais como instrumento de efetividade do desenvolvimento sustentável em Rio Verde, Goiás - Merida, Carolina (2014)
This research deals with the issue of economic valuation of ecosystem services based on positive incentive mechanisms as a strategy to stimulate the recovery and preservation of the environment, given the inefficiency of environmental protection currently used, primarily guided by command and control instruments. Taking as starting point the analysis of the interrelationship between the environment and sustainable development, the work also holds the examination of the legal issues underlying the use of payments for environmental services in Brazil. The chosen approach to face the issue concerns the study of the program Producer of Water", established under the Municipality of Rio Verde, Goias State, in order to verify the results obtained with respect to the recovery and preservation of riparian forests in around the headwaters of the Watershed of Abobora Stream, responsible for supplying approximately 70% of the population of that municipality. In summary, the question that this study seeks to answer relates to the effectiveness of payments for ecosystem services as a tool to promote sustainable development and social and environmental justice. The methodology has privileged the bibliographic research, in foreign and domestic literature, also drawing on the application of questionnaires to participants of "Producer of Water" program, Rio Verde, as well as the analysis of official data and documents obtained from the Department of Sustainable Economic Development of the Municipality of Rio Verde, Goias, and authoritative legal theory, focused on Machado (2012), Nusdeo (2012) and Altmann (2009).